Forest Fragmentation Shapes Resource Partitioning for Endemic Pollinators (Hymenoptera: Meliponini) - Bobadoye Bridget. O (International Journal of Entomology, 2019)
A field study was undertaken along six diverse habitat gradients of Kenya to evaluate the occurrence and underlining drivers that shape meliponine bee species diversity. These gradients ranged from continuous forest habitats (Indigenous forests, mixed forests and exotic forest patch) representing unfragmented habitats to dispersed habitats (Mixed deciduous woodlands, Grasslands dominated by perennial grasses such as Cenchrus ciliaris, Chloris roxburghiana and Acacia dominated bush lands) representing fragmented habitats respectively. A total of four different species of meliponine bees were encountered with Hypotrigona gribodoi being the most abundant species, followed by Meliponula ferruginea (black), Plebeina hildebrandti and Hypotrigona ruspolii in descending order. Occurrence and diversity of Hypotrigona gribodoi, Melipona ferruginea (black), Plebeina hildebrandti and Hypotrigonaruspolii was significantly influenced by the degree of fragmentation (vegetation type) and floral diversity (P = 0.0056); the mean number of colonies recorded per study site ranged from 2.3 in dispersed habitats in the lowlands to 1.0 in continuous forest landscapes in the highlands, whereas the mean population density ranged from 2.0 to 172 colonies/25 ha-transects. The results provide substantial support to better understand interactions between habitat structure and the degree of fragmentation in linking species diversity to habitat loss.
Keywords: meliponine bees